A UK based two-centre review of multifocality and its role in the treatment of papillary thyroid cancer. Issue 1 (January 2022) - Li, Lucy Qian; Hey, Shi Ying; Andreeva, Daria; Tornari, Chrysostomos; Sawant, Rupali; Harding, Noah Evans; Adamson, Richard; Hay, Ashley; Simo, Ricard; Nixon, Iain James
Abstract: Introduction: Multifocality is increasingly observed in papillary thyroid carcinoma (PTC) due to improvements in imaging and histopathological analysis. However, its significance in management, particularly as a sole risk-factor, remains controversial. This study aimed to investigate the prognostic value of multifocality in predicting recurrence following thyroid lobectomy in a contemporary group of PTC patients managed in the UK. Methods: Patients with PTC in NHS Lothian (2009-19) and Guys and St Thomas NHS Foundation Trust (2012-19) were identified. Categorical variables were compared using Chi-squared or Fisher's exact test. Five-year recurrence free survival (RFS) were analysed using Kaplan-Meier method and compared using log-rank. Results: Of 828 patients; 492 (59%) had unifocal and 336 (41%) multifocal disease on final pathology. A higher rate of pathological nodal disease (22%v36%, p < 0.001), total thyroidectomy (TT) (78%v92%, p < 0.001) and radioactive iodine (RAI) (57%v75%, p < 0.001) was demonstrated in patients with multifocality. With a median follow-up of 50 months, overall 5-year RFS was 96.5%; 96.5% for unifocal versus 96.6% for multifocal disease (p = 0.695). Recurrence was not shown to be associated with multifocality on either univariate or multivariate analysis. Amongst patients with T1/2N0M0 disease (n = 341), more patients were treated with TT and RAI with multifocal compared to unifocal disease (<0.001). Only two patients within this group recurred during follow up, both of whom had multifocal disease and were treated with TT and RAI (5yRFS100%v98.1%, p = 0.051). Conclusion: Multifocality is a common feature of PTC but does not appear to be an independent predictor of outcome. Therefore, treatment intensification on the basis of multifocality alone seems unwarranted. Highlights: The significance of multifocality, particularly as a sole risk factor, in the management of papillary thyroid cancer (PTC) is unclear Patients have excellent outcomes where multifocality is the only potential adverse risk factor (T1/2N0 disease) Clinicians should take an individualised approach to treatment that balances a small chance of oncological benefit with the risks for harm associated with further surgery, with or without radioactive iodine, if multifocal disease is identified